TRADISI KEILMUAN PESANTREN SALAFI - Muhammad Misbah (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
This article reveals the tradition in Salafi Islamic boarding school as a unindegineous Islamic istitution in Indonesia. This institution applies Wahabi school, do a purification movement, al-raj’u ila al-Qur’an wa al-Sunah, and exclusivity. The Salafi tradition is grouped into four concepts of thought: Syari’at, Bid’ah, Khurafat and Tahayul. It is intended to straighten the Muslim way of thinking in order to be good Muslims. Meanwhile the knowledge traditions are: in Fiqh, the books that are discussed are:al-Wajiz written by Syeikh abdul Adhim al-Badawi, Mulakhash fiqh by Syekh Fauzan, Sifat Shalat Nabi by Syeikh al-Bani, kitab Bulughul Maram. They all refuse everything that has no rules in Islamic law and opposite to the Islamic believe. The Salafi-Wahabi knowledge tradition that is always emphasize to the text authority and limits the idea’s role will cause the belief that al-Quran and hadis are perfect since they covers all life aspects of man. So, they made simplification that all religions that are not stated in al-Quran and hadis are believed as bid’ah. Meanwhile the doer is believed as a person who needs to be guidanced into the right way, by reminding or violence.